2019
DOI: 10.1101/752733
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Population-level sensitivity to landscape variables reflects individual-based habitat selection in a woodland bat species

Abstract: Understanding the relationship between habitat quality and population dynamics is fundamental for long-term management and range predictions in ecology. However, habitat suitability is generally only investigated at the individual scale, as it is the case for the lesser horseshoe bat (Rhinolophus hipposideros), a species of conservation concern. Using a statistical modelling approach and census data of 94 lesser horseshoe bat colonies located in Brittany (France), we analysed the effect of landscape compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
0
0
0
Order By: Relevance
“…radio tracking) and presence-absence data have shown that broadleaf woodland is the preferred foraging habitat for this species and strongly predicts the presence and size of colonies (Bontadina et al, 2002;Reiter, 2004a;Reiter et al, 2013;Tournant et al, 2013). The relationship between habitat quality and population dynamics was examined in further detail using detailed monitoring data from 94 colonies of the lesser horseshoe bat in Brittany, France (Jan et al, 2019b). Colony size, fecundity and growth rate were estimated for each colony in 2000-2014.…”
Section: Factors Known To Affect Population Demographymentioning
confidence: 99%
See 1 more Smart Citation
“…radio tracking) and presence-absence data have shown that broadleaf woodland is the preferred foraging habitat for this species and strongly predicts the presence and size of colonies (Bontadina et al, 2002;Reiter, 2004a;Reiter et al, 2013;Tournant et al, 2013). The relationship between habitat quality and population dynamics was examined in further detail using detailed monitoring data from 94 colonies of the lesser horseshoe bat in Brittany, France (Jan et al, 2019b). Colony size, fecundity and growth rate were estimated for each colony in 2000-2014.…”
Section: Factors Known To Affect Population Demographymentioning
confidence: 99%
“…These results build upon earlier studies and highlight the sensitivity of this species to deterioration of habitat quality around the colony, whether by urbanisation, agriculture (large open fields of crops) and habitat fragmentation. (Jan et al, 2019b).…”
Section: Factors Known To Affect Population Demographymentioning
confidence: 99%